Making HR technology decisions : a strategic perspective - Marler, Janet H. (Janet Hillirie); Fisher, Sandra L. (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2017)
This book examines how companies can use HR technology to extract value and potentially gain competitive advantage in a global marketplace. When HR technology was originally introduced, it was fairly easy for companies to see how using this technology could help them perform better than other companies. However, now that HR technology is so widespread, this distinctive value proposition is less clear. The goal of this book is to help HR managers and decision makers recognize where there is opportunity to capture value from HR technology, learn how to demonstrate that value, and navigate the many strategic decisions that must be made when choosing to implement an HR technology. We address topics such as how HR technology may deliver strategic value; whether to outsource HR processes, HR technology, and implementation project management; training and change management; how to measure value through conducting ROI analyses and using HR analytics; and, finally, how to evaluate and manage future HR technology innovations. We recognize that the landscape of HR technology solutions is constantly changing, and we had that in mind as we wrote this book. We do not focus on detailed technical reviews of specific HR software functionality or specific products or vendors. Instead, our approach is to introduce theoretical frameworks from various fields of management science to serve as a guide for decision making about HR technology. These theoretical approaches provide a scientific basis and structure to analyzing business challenges and increase the likelihood of making better decisions compared with using intuition or relying on vendor best practices. The theories and frameworks used in this book come from many different disciplines, including strategic management, economics, accounting, finance, organizational behavior, and information systems. This breadth helps managers understand the many different ways in which HR technology decisions can increase value by taking a strategic perspective.
1. Introduction -- 2. The value proposition: a strategic perspective -- 3. Organizational boundaries: insourcing or outsourcing decisions -- 4. Training and change management -- 5. Measuring value creation -- 6. Innovation: the next big thing -- Index.
Includes bibliographical references and index.
Title from PDF title page (viewed on March 3, 2017).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Personnel management -- Data processing; e-HRM; HR analytics; HRIS; HR innovation; HR technology; strategic HRM; Electronic books